2013
DOI: 10.1007/s10551-013-1957-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interactive Corporate Social Responsibility Communication on Corporate Reputation

Abstract: Companies increasingly communicate about corporate social responsibility (CSR) through interactive online media. We examine whether using such media is beneficial to a company's reputation. We conducted an online experiment to examine the impacts of interactivity in CSR communication on corporate reputation and word-of-mouth intentions. Our findings suggest that an increase in perceived interactivity leads to higher message credibility and stronger feelings of identification with the company, which also boost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
197
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(220 citation statements)
references
References 46 publications
10
197
1
12
Order By: Relevance
“…In fact, the database Web of Science reports only 35 studies on both concepts (corporate social responsibility and reputation) in the title together from 2010 to 2017, with effects in both directions. There are studies that find that prior corporate reputation has an impact on how consumers evaluate CSR Elisa Baraibar-Diez / Ladislao Luna SotorrĂ­o activities (Lee, Chang, Kim, & Lee, 2016;Skard & Thorbjornsen, 2014) but the major stream refers to the effect of CSR on corporate reputation (Brammer & Pavelin, 2004;Eberle, Berens, & Li, 2013;FernĂĄndez SĂĄnchez, Luna Sotorrio, & Baraibar Diez, 2015;Fombrun & Shanley, 1990;Kim, 2015;Luna & Baraibar, 2011;Melo & Garrido-Morgado, 2012;Odriozola, MartĂ­n, & Luna, 2015;Toms, 2002). That is why it is considered as a circular relationship (Olmedo, MartĂ­nez, Arcas, & Longuinos, 2012), although there are also studies from other points of view, considering reputation as a mediator between CSR and brand performance (Lai, Chiu, Yang, & Pai, 2010), financial performance (Saeidi, Sofian, Saeidi, Saeidi, & Saaeidi, 2015), or multiple stakeholder outcomes (Arikan, Kantur, Maden, & Telci, 2016).…”
Section: Csr Transparency and Corporate Reputationmentioning
confidence: 99%
“…In fact, the database Web of Science reports only 35 studies on both concepts (corporate social responsibility and reputation) in the title together from 2010 to 2017, with effects in both directions. There are studies that find that prior corporate reputation has an impact on how consumers evaluate CSR Elisa Baraibar-Diez / Ladislao Luna SotorrĂ­o activities (Lee, Chang, Kim, & Lee, 2016;Skard & Thorbjornsen, 2014) but the major stream refers to the effect of CSR on corporate reputation (Brammer & Pavelin, 2004;Eberle, Berens, & Li, 2013;FernĂĄndez SĂĄnchez, Luna Sotorrio, & Baraibar Diez, 2015;Fombrun & Shanley, 1990;Kim, 2015;Luna & Baraibar, 2011;Melo & Garrido-Morgado, 2012;Odriozola, MartĂ­n, & Luna, 2015;Toms, 2002). That is why it is considered as a circular relationship (Olmedo, MartĂ­nez, Arcas, & Longuinos, 2012), although there are also studies from other points of view, considering reputation as a mediator between CSR and brand performance (Lai, Chiu, Yang, & Pai, 2010), financial performance (Saeidi, Sofian, Saeidi, Saeidi, & Saaeidi, 2015), or multiple stakeholder outcomes (Arikan, Kantur, Maden, & Telci, 2016).…”
Section: Csr Transparency and Corporate Reputationmentioning
confidence: 99%
“…Fombrun 2005) and that communicating CSR efforts and activities can improve corporate reputation (c.f. Eberle et al 2013). A study by Godfrey et al (2009, p. 442) concluded that 'good deeds appear to earn chits.…”
Section: Is the Csr Giving Capability Valuable?mentioning
confidence: 99%
“…Second, we study the dynamics between insider and outsider stakeholders and the inter-level relation between activist groups and consumers. Last, we contribute to the ongoing discussion on the use of digital media, such as social media, to engage consumers in CSR from both activist groups' and firms' perspective Eberle et al 2013;Lyon and Montgomery 2013;Palazzo and Basu 2007;Schultz et al 2013;Whelan et al 2013). …”
Section: Summary Of Findings and Scientific Implicationsmentioning
confidence: 98%
“…The effect of online negative information on consumer attitude has been well studied in relation to consumers sharing their negative experiences about firms, i.e., negative electronic word-of-mouth (negative eWOM) (Eberle et al 2013). These studies find that negative eWOM has a stronger effect than positive eWOM, indicating that bad news about a firm is somehow conspicuous and influences how consumers feel about the firm in question.…”
Section: The Effect Of Online Protests On Consumers' Imagementioning
confidence: 99%